1997
DOI: 10.1002/(sici)1096-9071(199702)51:2<115::aid-jmv5>3.3.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of antibodies to human caliciviruses (HuCVs) in Kuwait established by ELISA using baculovirus‐expressed capsid antigens representing two genogroups of HuCVs

Abstract: Baculovirus recombinant-expressed antigens of Norwalk viruses (rNV) and a Mexico strain (rMX) of the Snow Mountain serogroup of human caliciviruses (HuCVs) were used in enzyme immunoassays to study the antibody prevalence among the Kuwaiti population and foreign workers employed in Kuwait. The antibody titers in 16 different age groups which ranged from neonates to centenarians were investigated by testing eight different dilutions of each serum (1:200-1:25,600). The results indicate that NV infection is wides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 2 publications
2
18
0
1
Order By: Relevance
“…In the present study, the overall prevalence of antibody to the three NVs among the study population was high, a finding that is comparable to most of the studies performed in other developing countries (5,20,31). However, the prevalence of antibody to MxV was lower in our study than the data reported by Jing et al in a study on a population in the Beijing area, in which high prevalences of antibody to both Norwalk and MxV viruses were observed (25).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the present study, the overall prevalence of antibody to the three NVs among the study population was high, a finding that is comparable to most of the studies performed in other developing countries (5,20,31). However, the prevalence of antibody to MxV was lower in our study than the data reported by Jing et al in a study on a population in the Beijing area, in which high prevalences of antibody to both Norwalk and MxV viruses were observed (25).…”
Section: Discussionsupporting
confidence: 89%
“…NVs are commonly detected in stool specimens of children with acute gastroenteritis at inpatient and outpatient clinics, indicating that NVs may cause severe gastroenteritis in children that requires hospitalization or a physician visit. Seroepidemiology studies also showed that children acquire antibodies to NVs at early ages, and the antibody prevalence continued to increase during the school years to adulthood (4,5,9,25,33). The antibody prevalence is generally higher in developing countries than in developed countries.…”
mentioning
confidence: 98%
“…We therefore speculate that secretor-negative individuals might be genetically resistant to a variety of norovirus strains, not just NV. However, most adult humans have serum antibody against noroviruses regardless of their secretor status (14,16,39,45; C. Moe et al, unpublished data), suggesting that some norovirus strains might be able to infect secretornegative individuals. In support of these observations, VLPs of one particular norovirus stain (VA207) bound to saliva from secretor-negative individuals (31), although the VLPs also bound modestly to saliva from secretor-positive individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Seroepidemiologic studies suggest that the adult cases of acute sporadic gastroenteritis that defy diagnosis may be caused by atypical rotaviruses, such as group C rotavirus [9] and caliciviruses [10].…”
Section: Acute Gastroenteritismentioning
confidence: 99%